Y=4-(2x/3)
2x-y=4
At the x-intercept, y = 0 So, from the equation, 2x + 0 = 12 or x = 6 So the x-intercept is (6,0)
Slope-Intercept Form: y = -2x +1
y=-2x+9
Y=4-(2x/3)
x-intercept: 6; y-intercept: 3
2x-y=4
At the x-intercept, y = 0 So, from the equation, 2x + 0 = 12 or x = 6 So the x-intercept is (6,0)
The y intercept is 1
Slope-Intercept Form: y = -2x +1
y=-2x+9
It is: y = -2/3x+4 in slope intercept form
it is -4
19
The slope is -2x and the y intercept is 5 Note that it will be a negative slope.
y = -2x+5 Slope: -2 Intercept: 5